2019
DOI: 10.12998/wjcc.v7.i23.4163
|View full text |Cite
|
Sign up to set email alerts
|

Pure squamous cell carcinoma of the gallbladder locally invading the liver and abdominal cavity: A case report and review of the literature

Abstract: BACKGROUNDGallbladder squamous cell carcinoma (GBSCC) is a rare subtype of malignancy and accounts for only 2%-3% of gallbladder malignancies. Due to its rapid development, most patients with GBSCC initially present with an advanced stage of the disease and hence a poor prognosis. The clinicopathological and biological features of SCC remain to be fully elucidated, owing to its uncommon occurrence. The majority of currently available data only described individual case reports or series analyses of trivial cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…Current description about the biological behaviour and outcome of pure SCC of the gallbladder is mainly based on case reports and/or small retrospective studies, therefore lacking statistical power. [3][4][5][6][7][8][9][10][11][12][13][14] Using the SEER registry, a large population-based database, we demonstrated that survival of patients with pure SCC was significantly shorter than that of patients with ASC, and their clinicopathological features and prognostic factors were also significantly different, which can discriminate pure SCC and ASC as two distinct entities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Current description about the biological behaviour and outcome of pure SCC of the gallbladder is mainly based on case reports and/or small retrospective studies, therefore lacking statistical power. [3][4][5][6][7][8][9][10][11][12][13][14] Using the SEER registry, a large population-based database, we demonstrated that survival of patients with pure SCC was significantly shorter than that of patients with ASC, and their clinicopathological features and prognostic factors were also significantly different, which can discriminate pure SCC and ASC as two distinct entities.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, there is little knowledge about pure squamous cell carcinoma (SCC) of the gallbladder because of its rarity, accounting for only 2-3% of all GBC cases. 3 Some published studies described the biological behaviour of pure SCC of the gallbladder as local infiltration, less lymphatic metastasis and a worse prognosis as compared with AC and adenosquamous carcinoma (ASC). But as all these studies were based on clinical case reports, the results showed limited statistical power.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations